Depression in cancer patients undergoing chemotherapy in a tertiary care hospital of North Bengal, India - Sutanay Bhattacharyya; Sharmistha Bhattacherjee; Tanuka Mandal; Dilip Kumar Das (Wolters Kluwer Medknow Publications, 2017)
Background: Detection of cancer and subsequent chemotherapy can lead to clinical depression in many cancer patients. Objectives: The study was conducted to find out the extent of depression in cancer patients undergoing chemotherapy and determine the factors associated with depression. Methods: A cross-sectional descriptive study was conducted at the Chemotherapy Day Care Centre of North Bengal Medical College and Hospital from May to June 2013. A total of 174 cancer patients were selected and interviewed after obtaining informed consent and Institutional Ethics Committee Clearance. Brief Edinburgh Depression Scale was used to find out depression with a score of 6 and above indicating depression. Data obtained was analyzed using SPSS software version 20. Logistic regression was used to see the relative importance of multiple contributing factors toward depression. Results: Out of 174 cancer patients, 97 (55.7%) were found to be depressed. Depression was comparatively higher in patients ≥50 years; in males; those belonging to religion other than Hindus; who received higher education; had monthly family income ≥5000 rupees and were involved in moderate or heavy work. Nearly 70.6% of blood cancer patients; 64.3% of those who had been receiving chemotherapy for ≥6 months and 56.9% of those in their 4th or less cycle of chemotherapy were found to be depressed. Conclusion: The study revealed depression is substantially high among cancer patients undergoing chemotherapy in this area. Diagnosis and treatment of cancer patients need to be complemented by psychological support for the cancer patients.